RED RICE CONSUMER PURCHASE DECISION WITH MARKETING MIX APPROACH AND CONSUMER BEHAVIOUR - Rahmat Taufiq Dwi Jatmika; Nisa Anjani; Ismi Ajeng (Jurnal Administrasi Bisnis (JUBIS), 2022)
Red rice is a product that has many benefits that are also sought after by the community. Red rice itself has good competitiveness if it is perfectly developed in the marketing mix used by the company. Consumer purchasing decisions are basically determined by how the organization or institution perfectly uses the marketing mix strategy. This article will examine how the Institute from the consumer's point of view of the use of the marketing mix that has been carried out and also its impact on purchasing decisions from consumers. The result of this article is the influence of the marketing mix which is influential but not significant on purchasing decisions. These results are because Red rice producers have not implemented the marketing mix perfectly. The conclusion and suggestion is that producers are more focused on developing the existing marketing mix in order to attract more consumers of Red rice in Cianjur Regency.